1988
DOI: 10.1001/archderm.1988.01670060035012
|View full text |Cite
|
Sign up to set email alerts
|

The Treatment of Port-wine Stains by the Pulsed Dye Laser

Abstract: A flashlamp-pumped pulsed dye laser at 577 nm was evaluated in the treatment of port-wine stains. The degree of lesional lightening was compared following laser exposure with pulse durations of 20 and 360 microseconds. In addition, lesional therapy using the 360-microseconds pulse duration was evaluated for lightening and side effects following long-term patient observation and after repeated treatments of the same site. A total of 52 patients with port-wine stain were treated; their average age was 29 years, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
0

Year Published

1991
1991
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(50 citation statements)
references
References 21 publications
2
48
0
Order By: Relevance
“…Several articles studying the use of the PTDL in the treatment of various dermatological lesions have reported minimal to no side effects, such as scarring, bleeding, pain, abscess formation, and infection [7,8,[13][14][15][16]. This aspect of the PTDL was confirmed during this investigation, thereby making it a potentially more attractive mode of treatment for warts.…”
Section: Discussionsupporting
confidence: 71%
“…Several articles studying the use of the PTDL in the treatment of various dermatological lesions have reported minimal to no side effects, such as scarring, bleeding, pain, abscess formation, and infection [7,8,[13][14][15][16]. This aspect of the PTDL was confirmed during this investigation, thereby making it a potentially more attractive mode of treatment for warts.…”
Section: Discussionsupporting
confidence: 71%
“…In a single case, a hypertrophic scar was reported by Swinehart [13]. Garden et al [6] reported the development of a 3 x 2 mm pyogenic granuloma in the area of laser therapy after 6 weeks of treatment of a PWS.…”
Section: Introductionmentioning
confidence: 93%
“…Following treatment with the FPDL, superficial blood vessels demonstrate agglutinated blood cells, fibrin and platelet thrombi confined to the papillary and reticular dermis with little or no damage to the sur rounding dermis, epidermis and adnexal structures [3]. These advantages of the FPDL have been confirmed by clinical results in numerous studies in the treatment of portwine stains (PWS), telangiectases and hemangiomas in children [4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…If a major proportion of the endothelial surface remains viable after laser irradiation, recanalisation is likely to occur. This may be an explanation for the observed reduced efficacy of the pulsed dye laser on the higher grades of PWS, i.e., those composed of significantly larger vessels [22]. A laser that can deliver yellow light for a period of time longer than the thermal relaxation time of the vessels (Table 1), but a time still short enough that thermal damage to nonvascular structures will be minimal, may offer considerable advantages for treating cutaneous lesions composed of larger vessels.…”
Section: Introductionmentioning
confidence: 98%